6p=12p+12

Simple and best practice solution for 6p=12p+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p=12p+12 equation:


Simplifying
6p = 12p + 12

Reorder the terms:
6p = 12 + 12p

Solving
6p = 12 + 12p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-12p' to each side of the equation.
6p + -12p = 12 + 12p + -12p

Combine like terms: 6p + -12p = -6p
-6p = 12 + 12p + -12p

Combine like terms: 12p + -12p = 0
-6p = 12 + 0
-6p = 12

Divide each side by '-6'.
p = -2

Simplifying
p = -2

See similar equations:

| 2(2x+3)=-4+2(2x+5) | | 8+5(x+3)+7x= | | log(2x+3)=3 | | r=780d+-13dt | | 8(m-9)=24 | | 3x+6x^2-5x-x^2= | | Sin^2(x)+3sinx-4=0 | | 3g=57 | | -12-w=45 | | 100x-x=12 | | -v+118=182 | | 0.4x+3.9=-5.78 | | (3x+6)(3x+7)=0 | | 5g-6-5-5g= | | 0.75n=46.50 | | -x-4+9=6x-4 | | -x+222=75 | | 34=225-v | | 8x+17=7x+10 | | 0.375n=9 | | 7=8w-w | | (2x+6)+42=180 | | 21+3x-7(2-3x)=4(x-5)+3x+27 | | 0.6c=-5.66 | | J=B+Brt | | 5x=-2-8 | | -5-6x=4(5x+3) | | tw+tq=u | | 0.66=2.66b | | uw+uq=u | | 5x=2-8 | | .5x-11=.1(x+10) |

Equations solver categories